Analysing oxygen reduction electrocatalysis on transition metal doped niobium oxide(110). Issue 28 (6th July 2022) - Abraham, Christina Susan; Anand, Megha; Kelly, Sara R.; Wang, Zhenbin; Nørskov, Jens K.
Abstract : Transition metal doped into Nb2 O5 (110) improves the conductivity of the system but has negligible influence on the ORR activity. Abstract : A good oxygen reduction reaction (ORR) catalyst should be stable and active under electrochemical reaction conditions. Niobium pentaoxide (Nb2 O5 ) is known to be stable under ORR conditions. However it has a large band gap, which makes conductivity a challenge during the reaction. In this work, we aim to understand if surface modification of the 110 facet of niobium pentaoxide with transition metal doping has any effect on its ORR activity and conductivity. While the problem of conductivity in the case of transition metal oxides (TMOs) can be partially rectified by transition metal doping, it has negligible influence on the ORR activity of the doped systems.